THE MULTIATTRIBUTE CONSTRUCTION OF THE SUBJECT OF MODERN MARKETING - M. Kalynychenko (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
The paper presents the results of research marketing subject as an object of scientific knowledge. Existing definitions of the subject marketing in modern specialized literature were systematized. The essence of the main characteristics and attributes (structure) of the subject of marketing is determined; the features of marketing are highlighted in the narrow and broad sense. The author's definition of marketing subject is given including within the process and system approaches. It considers also the set of characteristics and attributes which reflect all possible objects of knowledge in marketing.